ANALISIS KUALITAS AIR TANAH UNTUK KONSUMSI PADA LERENG VOLKAN DAERAH KLATEN JAWA TENGAH - Alif Noor Anna; Suharjo -; Retno Woro Kaeksi; Rudiyanto - (Universitas Muhammadiyah Semarang, 2015)
Groundwater is a natural resource that must be managed and preserved well. Monitoring of groundwater quality essential as vulnerable ground water pollution, so the quality is declining, which in turn can not be used for domestic and non-domestic purposes. The aim of this study is to analyze the quality of groundwater in the volcanic slope of district Klaten, Central Java. The research method that used is survey. The analysis of the results based on the quality standard ofdrinking water in accordance PERMENKES No. 907/Menkes/SK/VII/2002. The data which collected are land form, shallow groundwater data, groundwater pressure, and springs. The results were obtained: (1) the landforms in Klaten are divided into four units, namely slopes and volcanic peaks, volcanic foot, volcanic fluvial plains, and a structural, (2) the quality of shallow groundwater in Klaten is under the standard that is set by PERMENKES No. 907/Menkes/SK/VII/2002 or it can be consumed.Keywords: groundwater quality, land form, volcanic slope, Consumption